Evaluation of Specific Intervention Programs on Pregnant Women with Chronic Energy Deficiency to Reduce the Incidence of Stunted Children - Sarwan Payanadi; Sastrawan; Sismulyanto (Green Publisher Indonesia, 2024)
The West Lombok Regency implementation interventions and sensitive interventions to reduce stunting 3.73 percent from 2021 to 2022. The research aims to determine if there is a significant relationship between specific intervention programs for chronically energy-deficient pregnant women and the reduction of stunting incidents. The objective is to evaluate the impact of specific intervention programs on pregnant women with chronic energy deficiency. The quantitative cross-sectional method involved 294 respondents, with the research conducted from September to November 2023. Conclusions: (1) There is a significant relationship with the provision of supplementary food, with an odds ratio of 0.264 times. (2) There is a significant relationship with the provision of blood supplement tablets, with an odds ratio of 0.379 times. (3) There is no relationship with pregnancy examinations. (4) There is a significant relationship with the administration of TT/TD immunizations, with an odds ratio of 0.440 times. (5) There is no relationship with HIV/TB/Malaria/Hepatitis services. (6) There is no relationship with the mother's class program. (7) Independent variables explain the dependent variable by 17.5 percent, and 82.5 percent is explained by variables not studied. Recommendations for the West Lombok Regency government: The provision of supplementary food requires intensive monitoring of the target population. Increasing the coverage of pregnancy examination programs and blood tablet consumption requires an application system. Increasing the coverage of TT/TD immunization integrated with a health application. HIV/TB/Malaria/Hepatitis services require human resource planning, equipment and disposable material, and reporting systems. Mother's class activities require innovation and modification.